2012
DOI: 10.1371/journal.pone.0041891
|View full text |Cite
|
Sign up to set email alerts
|

Rabring7 Degrades c-Myc through Complex Formation with MM-1

Abstract: We have reported that a novel c-Myc-binding protein, MM-1, repressed E-box-dependent transcription and transforming activities of c-Myc and that a mutation of A157R in MM-1, which is often observed in patients with leukemia or lymphoma, abrogated all of the repressive activities of MM-1 toward c-Myc, indicating that MM-1 is a novel tumor suppressor. MM-1 also binds to the ubiquitin-proteasome system, leading to degradation of c-Myc. In this study, we identified Rabring7, a Rab7-binding and RING finger-containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 34 publications
0
22
1
Order By: Relevance
“…It favours c-Myc degradation by recruiting the ubiquitin ligase Skp2–ElonginC–ElonginB–Cullin2 complex, and driving it to the proteasome via the 26S subunit Rpt3 [54] (figure 3 b ). The monoubiquitination of PFDN5 by Rabring7, a Rab7-binding and RING finger-containing protein, stimulates this second role of PFDN5 in the control of c-Myc [55] (figure 3 b ). In addition, PFDN5 and the Egr-1 repressor bind and downregulate the promoter of the wnt4 gene.…”
Section: Prefoldin Plays Transcriptional Rolesmentioning
confidence: 99%
“…It favours c-Myc degradation by recruiting the ubiquitin ligase Skp2–ElonginC–ElonginB–Cullin2 complex, and driving it to the proteasome via the 26S subunit Rpt3 [54] (figure 3 b ). The monoubiquitination of PFDN5 by Rabring7, a Rab7-binding and RING finger-containing protein, stimulates this second role of PFDN5 in the control of c-Myc [55] (figure 3 b ). In addition, PFDN5 and the Egr-1 repressor bind and downregulate the promoter of the wnt4 gene.…”
Section: Prefoldin Plays Transcriptional Rolesmentioning
confidence: 99%
“…It interacts with Tetherin, a membrane-anchored protein that retains HIV-1 particles during the final phase of viral replication, and promotes internalization and degradation of these particles [16]. It also has a role in the regulation of Epidermal Growth Factor Receptor (EGFR) trafficking for lysosomal degradation [17] and assists in the degradation of the proto-oncogene c-Myc through a complex with MM-1, which is a tumor suppressor that binds to the myc box II [18]. A Rabring7/BCA2-like protein is present in vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was reported that RNF115 targets p21 for ubiquitin‐mediated degradation to promote breast cancer cell proliferation . In addition, RNF115 has been shown to stimulate ubiquitination and degradation of c‐Myc and epidermal growth factor receptor in other model systems . Interestingly, we found that depletion or overexpression of RNF115 does not affect USP9X protein abundance (Figure ).…”
Section: Discussionmentioning
confidence: 65%
“…13 In addition, RNF115 has been shown to stimulate ubiquitination and degradation of c-Myc and epidermal growth factor receptor in other model systems. 32,33 Interestingly, we found that depletion or overexpression of RNF115 does not affect USP9X protein abundance (Figure 2). In support of our findings, a recent study showed that SMURF1, a member of the Nedd4 family of HECT ubiquitin ligases, interacts with USP9X but this association does not lead to USP9X degradation.…”
Section: Discussionmentioning
confidence: 85%